The Effect of Psychological Contracts: Transactional, Relational, Balance on Organizational Citizenship Behaviors University Staff in Indonesia and Malaysia (International Journal of Scientific Research and Management (IJSRM), 2021)
Organization Citizenship Behavior is an extra-role individual behavior that is discretionary which is not directly recognized by the formal reward system and will jointly encourage organizational functions. Psychological contracts and their fulfillment are linked to employee responses consisting of intra-role and extra-role performance. The purpose of this study was to determine the effect of the transactional contract, relational contract, and balance contract on organizational citizenship behavior. The sample in this study was 313 university staff in Indonesia and universities in Malaysia. Data collection used a psychological contract scale and a scale of organizational citizenship behavior. The result of this study is that there is a significant influence between the relational contract and balance contract on organizational citizenship behavior. Meanwhile, there is no effect of the transactional contract on organizational citizenship behavior.